Evaluation of alternatives for increasing the capacity of intersections - Nair, K. Thanappan; Drew, Donald R.; Jones, John Hugh; Pakorn Adulbhan; Government of Australia (Bangkok : Asian Institute of Technology, 1972)
The capacity of a street network is often limited by the capacity of critical intersections which rapidly become bottlenecks in peak conditions. Traffic congestion in a city tends to centre around these intersections. co- ordinated route control. The congestion can be relieved by The capacity of intersections can be increased by using suitable peripheral roads so as to form intersect ion complexes through which platoons of vehicles can be orderly and continuously guided by co-ordinated traffic signals. The principle is one of exploiting more than one gap in the cross traffic. The capacity of such an intersection complex was found to be up to four times that of an ordinary intersection. The effect of diffusion of platoons was investigated and was found not to be critical. The delay and queues were low in comparison with signalized intersections for various diffusion constants. The introduction of this principle to both existing and new city networks was found to be positive. Investigations included the applicability of the principle to roundabouts and other existing network geometrics, as well as to various potential innovative grid networks for new cities.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1972
Keywords: Urban transportation; City traffic